Low cost optical multi-touch tables: projected versus LCD optical - Ramón Más Sansó; María José Abásolo Guerrero; Armando Eduardo De Giusti; Cristian García-Bauzá; Marcelo Vénere; Cristina Manresa Yee (Journal of Computer Science and Technology, 2013)
Based on our experience, in this paper we present the main aspects of two different approaches to implement low cost multi-touch tables: projection based and LCD based. The former uses a video projector to build a feedback image on the surface of a multi-touch table and the latter uses an LCD display for the same purpose. We discuss the main advantages and disadvantages we have faced during our design and building experiences